Bernstein-type theorems in hypersurfaces with constant mean curvature - MANFREDO P. DO CARMO (Anais da Academia Brasileira de Ciências, 2000)
By using the nodal domains of some natural function arising in the study of hypersurfaces with constant mean curvature we obtain some Bernstein-type theorems.